Human detection and tracking for video surveillance system - Shafie, Amir Akramin; Khalifa, Othman Omran; Ali, M. H.; Mat Ali, Roslizar (2010)
Recent research in video surveillance system has shown an increasing focus on creating reliable systems utilizing non-computationally expensive technique for observing humans’ appearance, movements and activities, thus providing analytical information for advanced human behavior analysis and realistic human modeling. In order for the system to function, it requires robust method for detecting human form from a given input of video streams.